2022
DOI: 10.1038/s41541-022-00492-y
|View full text |Cite
|
Sign up to set email alerts
|

An epitope-optimized human H3N2 influenza vaccine induces broadly protective immunity in mice and ferrets

Abstract: There is a crucial need for an improved H3N2 influenza virus vaccine due to low vaccine efficacy rates and increased morbidity and mortality associated with H3N2-dominated influenza seasons. Here, we utilize a computational design strategy to produce epitope-optimized, broadly cross-reactive H3 hemagglutinins in order to create a universal H3N2 influenza vaccine. The Epigraph immunogens are designed to maximize the viral population frequency of epitopes incorporated into the immunogen. We compared our Epigraph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Here, we report a vaccine strategy that utilizes a computational algorithm to maximize potential epitopes incorporated into the immunogen design and provide broad protection against antigenically diverse IBV. Our group has previously demonstrated the utility of Epigraph HA immunogens against swine H3 [ 28 ] and human H3 influenza A virus [ 29 ] and here we show similar improved cross-reactive efficacy when applied to IBV. Mice immunized with IBV-Epi developed highly cross-reactive HI and neutralizing antibody responses.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Here, we report a vaccine strategy that utilizes a computational algorithm to maximize potential epitopes incorporated into the immunogen design and provide broad protection against antigenically diverse IBV. Our group has previously demonstrated the utility of Epigraph HA immunogens against swine H3 [ 28 ] and human H3 influenza A virus [ 29 ] and here we show similar improved cross-reactive efficacy when applied to IBV. Mice immunized with IBV-Epi developed highly cross-reactive HI and neutralizing antibody responses.…”
Section: Discussionsupporting
confidence: 74%
“…Further, an important note for this study is that direct comparison of our hexavalent Epigraph vaccine and quadrivalent Fluzone is not entirely equivalent due to the differences in valency. We have previously interrogated the contribution of individual Epigraph immunogens targeting human H3 IAV, and observed that the first and second Epigraph HA proteins induced the strongest cross-reactive antibody responses, and the third Epigraph HA protein elicited strong cross-reactive T cell responses [ 29 ]. These data indicate that each Epigraph HA protein is uniquely contributing to immunity and a trivalent cocktail is likely necessary to provide broadly cross-reactive responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, there were no significant differences among the various multivalent vaccine formulations, regardless of whether antigens were mixed in equal proportions or with a specific antigen dominant proportion. All vaccines demonstrated sufficiently robust levels of protection against infection [ 20 ]. Furthermore, the results of our immunoglobulin analyses revealed that the expression of immunoglobulins increased in the experimental groups administered with the multivalent vaccines compared to the monovalent vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In M7-CpG NP-vaccinated mice, 100% survival was achieved in the HK/ 68 challenge model, an event only achieved in this experimental group with the CpG group also illustrating considerable survival (70%). epitope-based vaccines induced protection in ferrets and mice a total clearance of H3N2 in lungs (8,73).…”
Section: Discussionmentioning
confidence: 99%